Clinical chimeric antigen receptor‐T cell therapy: a new and promising treatment modality for glioblastoma. Issue 5 (20th May 2019) - Brown, Michael P; Ebert, Lisa M; Gargett, Tessa
Abstract: Chimeric antigen receptor (CAR)‐T cell therapy is now approved in the United States and Europe as a standard treatment for relapsed/refractory B‐cell malignancies. It has also been approved recently by the Therapeutic Goods Administration in Australia and may soon be publicly reimbursed. This advance has accentuated scientific, clinical and commercial interest in adapting this exciting technology for the treatment of solid cancers where it is widely recognised that the challenges of overcoming a hostile tumor microenvironment are most acute. Indeed, CAR‐T cell technology may be of the greatest value for those cancers that lack pre‐existing immunity because they are immunologically 'cold', or have a low somatic tumor mutation load, or both. These cancers are generally not amenable to therapeutic immune checkpoint blockade, but CAR‐T cell therapy may be effective because it provides an abundant supply of autologous tumor‐specific T cells. This is achieved by using genetic engineering to re‐direct autologous T‐cell cytotoxicity towards a tumor‐associated antigen, bypassing endogenous T‐cell requirements for antigen processing, MHC‐dependent antigen presentation and co‐stimulation. One of the most challenging solid cancers is glioblastoma, which has among the least permissive immunological milieu of any cancer, and which is almost always fatal. Here, we argue that CAR‐T cell technology may counter some glioblastoma defences and provide a beachhead for furthering our eventual therapeutic aims of restoring effective antitumor immunity. Although clinical investigation of CAR‐T cell therapy for glioblastoma is at an early stage, we discuss three recently published studies, which feature significant differences in target antigen, CAR‐T cell phenotype, route of administration and tumor response. We discuss the lessons, which may be learned from these studies and which may guide further progress in the field. Abstract : Glioblastoma is a deadly disease without effective treatment. Recent clinical data indicate that chimeric antigen receptor (CAR)‐T cell therapy may provide a useful treatment approach.